Syncope during resistance exercise in an individual with type 1 diabetes. (30th August 2013) - Turner, D; Ayles, M; Gray, BJ; Luzio, S; Bain, SC; Rees, ED; West, DJ; Campbell, MD; Bastin, L; Bracken, RM
Abstract: Although metabolic and cardiovascular effects of resistance exercise in type 1 diabetes (T1DM) remain poorly explored, research employing type 2 diabetes suggests glycaemic and cardiovascular benefits. However, this intense exercise carries some risks. Here we describe the cardiovascular and metabolic responses of a newly diagnosed, previously sedentary T1DM individual experiencing syncope during an unaccustomed acute bout of resistance exercise. The cause of this exercise‐induced incident was attributed to inappropriate cardiovascular control and lack of habituation to accompanying acid‐base disturbances. Careful consideration of exercise intensity and progression in previously sedentary T1DM performing resistance exercise sessions is warranted. Copyright © 2013 John Wiley & Sons.